Genomic Plasticity Mediated by Transposable Elements in the Plant Pathogenic Fungus Colletotrichum higginsianum. (26th April 2019) - Tsushima, Ayako; Gan, Pamela; Kumakura, Naoyoshi; Narusaka, Mari; Takano, Yoshitaka; Narusaka, Yoshihiro; Shirasu, Ken
Abstract: Phytopathogen genomes are under constant pressure to change, as pathogens are locked in an evolutionary arms race with their hosts, where pathogens evolve effector genes to manipulate their hosts, whereas the hosts evolve immune components to recognize the products of these genes. Colletotrichum higginsianum ( Ch ), a fungal pathogen with no known sexual morph, infects Brassicaceae plants including Arabidopsis thaliana . Previous studies revealed that Ch differs in its virulence toward various Arabidopsis thaliana ecotypes, indicating the existence of coevolutionary selective pressures. However, between-strain genomic variations in Ch have not been studied. Here, we sequenced and assembled the genome of a Ch strain, resulting in a highly contiguous genome assembly, which was compared with the chromosome-level genome assembly of another strain to identify genomic variations between strains. We found that the two closely related strains vary in terms of large-scale rearrangements, the existence of strain-specific regions, and effector candidate gene sets and that these variations are frequently associated with transposable elements (TEs). Ch has a compartmentalized genome consisting of gene-sparse, TE-dense regions with more effector candidate genes and gene-dense, TE-sparse regions harboring conserved genes. Additionally, analysis of the conservation patterns and syntenic regions of effector candidate genes indicated that the two strains vary in their effector candidate gene sets because of de novo evolution, horizontal gene transfer, or gene loss after divergence. Our results reveal mechanisms for generating genomic diversity in this asexual pathogen, which are important for understanding its adaption to hosts.